Cancer and aging handbook : research and practice - Bellizzi, Keith M.; Gosney, Margot (Chichester, UK : Wiley-Blackwell, 2012)
First multidisciplinary book available that examines the cancer and aging interface. Include specific points about how cancer and aging interrelate to guide training, research, and intervention"--Provided by publisher.
pt. I. Cancer and aging in context -- pt. II. Strategies for cancer prevention in older adults -- pt. III. Cancer screening guidelines for older adults -- pt. IV. Cancer treatment -- pt. V. Common cancers in the elderly -- pt. VI. Cancer survivorship and aging -- pt. VII. End-of-life care -- pt. VIII. Emerging issues.
Includes bibliographical references.
Print version record.
Keywords: Cancer; Aging; Behavior modification; Health attitudes; Health behavior; Self-care, Health; HEALTH & FITNESS -- Diseases -- Cancer; MEDICAL -- Oncology; Aging; Cancer; Neoplasms -- prevention & control; Aged; Aging -- physiology; Neoplasms -- therapy; Electronic books